2022
DOI: 10.4062/biomolther.2021.077
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A Ameliorates Neuroinflammation in the MPTP and 6-OHDA-Induced Parkinson's Disease Models

Abstract: increasing evidence suggests that neuroinflammation may be a critical factor in the development of Parkinson's disease (PD) in addition to the ratio of acetylcholine/dopamine because dopaminergic neurons are particularly vulnerable to inflammatory attack. In this study, we investigated whether botulinum neurotoxin A (BoNT-A) was effective for the treatment of PD through its anti-neuroinflammatory effects and the modulation of acetylcholine and dopamine release. We found that BoNT-A ameliorated MPTP and 6-OHDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In other words, the suppression of cDVC A2 NA neurons has been robust enough to induce the release of the inflammatory markers, IL-6 and TNF-α, specifically in the PFC. The obtained data aligns with prior research that observed an increase in inflammatory markers in the 6-OHDA produced PD model ( Ham et al, 2022 , Tiwari et al, 2021 , Li et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
“…In other words, the suppression of cDVC A2 NA neurons has been robust enough to induce the release of the inflammatory markers, IL-6 and TNF-α, specifically in the PFC. The obtained data aligns with prior research that observed an increase in inflammatory markers in the 6-OHDA produced PD model ( Ham et al, 2022 , Tiwari et al, 2021 , Li et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
“…Most studies were performed in the 6-hydroxydopamine (6-OHDA) hemi-PD model. Only one study utilised the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD [ 25 ] (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…MPTP is a compound that is able to cause a selective degeneration of the SNPc after systemic administration and has been widely used in the last 30 years to obtain a PD animal model. In the only study we included in our selected studies that adopted this approach, the protocol consisted of an intraperitoneal injection four times per day for 7 days in C57BL/6 mice [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Release of substance P from dorsal-root ganglion neurons and stimulated release of CGRP from trigeminal ganglion neurons have been shown to be inhibited by the administration of botulinum toxin A 35 , 36 . Studies have also shown that botulinum toxin A may reduce the expression of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α, dampening the inflammatory process and reducing pain propagation resulting from peripheral stimuli 35 , 37 , 38 . These reductions in peripheral sensitization and afferent input to the spinal cord from peripheral nerve endings may indirectly decrease the central sensitization process.…”
Section: Discussionmentioning
confidence: 99%